(untitled) (AUN INTERNATIONAL CONFERENCE, 2024)
Modern communication systems enable the rapid development of microstrip patch antennas. Their lightweight and compact profile makes patch antennas increasingly popular today. They are easy to manufacture and seamlessly integrate into feeding networks, making them highly versatile for modern applications. This paper presents a single-feed, dual-band slotted antenna designed for 5G applications, operating in the 28 GHz and 38 GHz millimeter-wave bands with enhanced bandwidth. The antenna design uses a Rogers 5880 substrate with a relative permittivity of 2.2 and a loss tangent of 0.0009, modeled with CST software. The microstrip antenna measures 20 x 20 x 0.787 mm³ and features a cylindrical patch on top, with inner and outer radii of 3.00 mm and 4.32 mm, and a thickness of 0.787 mm. Initially, a cylindrical radiator is configured to resonate at 38 GHz; subsequently, a symmetrical four-cone slot is introduced on the cylindrical radiator to enable an additional resonant frequency at 28 GHz. Simulation results indicate reflection coefficients of -27.83 dB at 28 GHz and -49.47 dB at 38 GHz, with achieved bandwidths of 0.765 GHz in the lower band and 1.29 GHz in the upper band, and gains of 7.52 dBi and 6.67 dBi, respectively.